Praktik Bimbingan Konseling Kelompok Di Pondok Pesantren Darusy Syahadah Boyolali Tahun Pelajaran 2015/2016 - Munir, Misbakhul; , Dr. Mohamad Ali, S.Ag, M.Pd (2016)
The guidance and counseling service in Darusy Syahadah Boyolali Islamic Boarding School is hold on Islamic values with intensive activities. In providing guidance and counseling service, Darusy Syahadah Islamic Boarding School uses two methods, they are individual method and group method. Group method service uses group as media of guidance and counseling. In this method, the member can share their experience and motivate each other, so it can influence student's behaviour. The aim of this study is to describe the practice of group guidance and counseling in Darusy Syahadah Islamic Boarding School in the academic year of 2015/2016. This research uses field research, and the methods of collecting data are interview, observation, and documentation, while the method of data analysis is descriptive qualitative one. From this research, it can be concluded that : (1) Group guidance and counseling service in Darusy Syahadah Islamic Boarding School is called ḥalaqah (2) The aims of ḥalaqah is to discuss and to find a solution of students, and also to build Islamic student personality. (3) The themes of ḥalaqah are Akidah, Akhlak, Ibadah, self understanding, and conflict management. (4) Ḥalaqah held once a week around boarding school. The first meeting is focused in explaining the meaning, goal and activities of ḥalaqah, introduction between the members of group, and forming member structure. In the next stage, every meeting is always begun by reading al-Qur'an, than speech from one of member. In the main activity, musyrif explains a topic, than it continous continue with quiz and discuss between member. In the last activity, musyrif gives a time to member for consulting their problem. The result of ḥalaqah is analyzing to know the student progress. Key word : Guidance and counseling, Group method, Ḥalaqah